Avoiding the Unhappy Patient by Building Rapport in the Internet Age - Kern, Eugene; Friedman, Oren (Facial Plastic Surgery, 2019)
The dynamics of the doctor–patient relationship has been complicated as more patients seem to expect perfection in this age of selfies and Internet postings. The preoperative patient interview is critical to recognize both body language clues and subtle but apparent red flags to avoid rhinoplasty on potentially unhappy patients. This interview should include routine use of a body dysmorphic disorder screening questionnaire since legions of these patients are undiagnosed prior to surgery and few, if any, are ever satisfied with even an excellent surgical result. These patients need diagnosis and psychological intervention—not surgery. Rapport is critical to patient and surgeon's satisfaction; therefore, it is valuable to practice the ABC's of rapport building: 1) active listening, (2) positive body language, and (3) candor.
Keywords: aesthetic surgery; doctor–patient relationship; communication